2000
DOI: 10.1002/(sici)1521-4095(200005)12:9<640::aid-adma640>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Ordered Colloidal Nanoalloys

Abstract: Colloidal alloy superlattices of two different nanoclusters are demonstrated here for the first time. Thiol‐functionalized Ag and Au nanoclusters were prepared separately in toluene before mixing and solvent evaporation. For certain Au/Ag proportions, the particles spontaneously self‐organized into ordered 2D arrays, which can be seen in the bright field STEM image in the Figure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(50 citation statements)
references
References 0 publications
3
46
0
1
Order By: Relevance
“…Figure 8 shows a TEM image of an assembled monolayer of platinum nanoparticles forming a hexagonally closed packed structure. Similarly, Kiely et al (26,156) have shown that it is possible to produce ordered arrays from a bimodal distribution of sizes of the same metal and also using different metals as they formed AB 2 and AB superlattice arrays consisting of gold and silver nanoparticles. In their case, the size distribution of each metal fraction (A or B) was very narrow.…”
Section: Assembly Of Metal Nanoparticles and Their Collective Propertiesmentioning
confidence: 99%
“…Figure 8 shows a TEM image of an assembled monolayer of platinum nanoparticles forming a hexagonally closed packed structure. Similarly, Kiely et al (26,156) have shown that it is possible to produce ordered arrays from a bimodal distribution of sizes of the same metal and also using different metals as they formed AB 2 and AB superlattice arrays consisting of gold and silver nanoparticles. In their case, the size distribution of each metal fraction (A or B) was very narrow.…”
Section: Assembly Of Metal Nanoparticles and Their Collective Propertiesmentioning
confidence: 99%
“…This provided the ground work for the Kiely et al (2000), Shevchenko et al (2006aShevchenko et al ( , b, 2007, Chen et al (2007), DeVries et al (2007), Perepichka and Rosei (2007), and Su et al (2007) [ We derive the nanocompound nomenclature in this report by describing the combination of [Hn] elements (left to right horizontally) with [Hn] elements (vertically in descending order). A more systematic nomenclature based on these principles that describe stoichiometry, etc., should be expected to evolve from these basic principles Superscript numbers for nanocompounds [H-n:H-n] 1-13 above are keyed to literature references and correspond to the bold numbers noted in the nanocompound grid (Table 2) J Nanopart Res (2009Res ( ) 11:1251Res ( -1310Res ( 1271 construction of extended, 1D [H-1] n -type nanocompound examples in this category.…”
Section: Metal Nanocrystal-metal Nanocrystal: [H-1:h-1]-type Compoundsmentioning
confidence: 72%
“…1G). These results suggest that the size ratio is crucial for the formation of binary assemblies of nanoparticles (5)(6)(7)(8)(9)(10)14). To examine the packing symmetry of the binary superlattices obtained at ␥ ϭ 0.42, transmission electron microscopic (TEM) investigations along the various crystallographic directions were performed.…”
Section: Resultsmentioning
confidence: 98%
“…Two crucial parameters determine the binary assembly pattern of the spheres: (i) the size ratio (␥ ϭ R small ͞R large ) and (ii) the stoichiometric ratio between two spheres. Although the binary organization of colloidal nanoparticle systems can be predicted by such hard sphere assembly approximations (5)(6)(7)(8)(9)(10)14), other parameters such as interparticle potentials also contribute to the determination of assembly patterns (10,14).Binary superlattices of magnetic Fe 3 O 4 and Co nanoparticles were examined with careful consideration of such size ratio and stoichiometric ratio effects. The Fe 3 O 4 nanoparticles used are highly monodispersed ( Ϸ 5%), and the size can be tuned from 8.0 nm to 15.7 and 18.0 nm (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation